Role of Education and Mentorship in Entrepreneurial Behavior: Mediating Role of Self-Efficacy - Hu, Binwu; Zheng, Qiang; Wu, Jie; Tang, Zhibin; Zhu, Jianchun; Wu, Simin; Ling, Ying (Frontiers in Psychology, 2021)
Farmers have been very precious for societies for ages. Their active experiments, valuable knowledge about their surroundings, environment, and crops' requirements have been a vital part of society. However, the psychological perspectives have been a hole in the loop of farming. Hence, this study has investigated the antecedents of entrepreneurial behaviors of farmers with the mediating risk of their entrepreneurial self-efficacy. The population chosen for this study was the farming community of suburbs of China, and a sample size of 300 was selected for the data collection. This is a survey study where a structured questionnaire was adapted on a five-point Likert scale. The data was collected from the farming community to know their psychological and behavioral preferences about their profession. This study has produced interesting results that education, training, and intrinsic motivation play a vital role in farmers’ entrepreneurial self-efficacy, affecting their entrepreneurial behaviors. This study will add to the body of knowledge and provide an eminent path for emerging entrepreneurs to find more mentorship opportunities to overcome the limitations in upcoming endeavors influencing education and training.